Commitment of Iraqi Public Companies to Social Responsibility Accounting : A Case Study - Shumran Obaid Khlaif Alameer (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This research aimed to measure the extent of public sector companies' commitment to adopting social responsibility accounting in Wasit Textile and Knitting Factory as a model. The research concluded that the research sample had achieved advanced levels of adopting social responsibility accounting despite the limited capabilities of the research sample. It has yet to reach the required level of adopting social responsibility accounting. The research used the seven-point Likert scale to measure the extent of the research sample's commitment to adopting social responsibility accounting. Among the most important results reached by the study is the existence of accounting procedures and policies that are compatible with the requirements for adopting responsibility accounting by the research sample. The study recommended the full adoption of social responsibility accounting in industrial companies and others, due to its important role in achieving the goals of social responsibility as well as moving from the stage of voluntary commitment to the stage of commitment to social responsibility.